PENGARUH MINYAK ATSIRI TERHADAP PERTUMBUHAN Colletotrichum gloeosporioides (Penz.) Sacc. PENYEBEBAB PENYAKIT ANTRAKNOSA BUAH PEPAYA (Carica papaya L.) SECARA IN VITRO - Alberida, Heffi; Eliza, Eliza; Lova, Ria Nati (IAIN Batusangkar, 2014)
This study aims to determine the effect of atsiri oils on the growth of mycelium and formation of aservulus Colletotrichum gloeosporioides causes anthracnose disease of papaya fruits in vitro. This study is an experimental study, using a completely randomized design (CRD) 3 x 4 factorial with replicates. The treatments tested were types of essential oils (Citronella, Cinnamon and Clove) and volume (0,3 mL, 9 mL and 18 mL). Data were analyzed with ANOVA and further test used is BNJ at the level of 5 % for the diameter of the colony and DNMRT at the level of 5 % for the amount of aservulus Colletotrichum gloeosporioides. The results showed the essential oil can inhibit the growth of mycelium and formation of aservulus Colletotrichum gloeosporioides. Clove oil in 3 mL volumes can significantly inhibit the growth of mycelium with a diameter of 10.07 cm 13.77 cm whereas control. Mycelium growth were treated with clove oil is slower than the citronella oil (12.67 cm) and cinnamon oil (13.7 cm). Clove oil in 9 mL volume can significantly inhibit the formation of mold aservulus the number 71 aservulus while control aservulus 527.67. Aservulus formation of fungus treated with clove oil is slower than the citronella oil (116 aservulus) and cinnamon oil (263 aservulus).Key words : essential oils, Colletotrichum gloeosporioides, antraknosa